Telaah Gender terhadap Konsep Nafkah dalam Islam: Antara Tanggung Jawab Suami dan Kontribusi Istri - Mitha Shaskila Sinaga (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Social and economic transformations have increased wives’ involvement in meeting household needs, although Islamic law normatively places the primary obligation of family maintenance on husbands. This development raises questions concerning the legal status of wives’ economic contributions, their rights over personal income, and the distribution of domestic responsibilities within the family. This study aims to analyze the Islamic concept of maintenance, husbands’ responsibilities, wives’ economic contributions, and the division of marital roles from the perspectives of gender theory and Maqashid al-Shari’ah. This qualitative study employs library research by examining the Qur’an, Hadith, Islamic jurisprudential literature, legal regulations, books, and relevant journal articles. The collected data are examined using qualitative content analysis. The findings demonstrate that the primary obligation to provide maintenance remains with the husband and is not automatically transferred to the wife, even when she is employed or earns a higher income. A wife’s financial contribution is voluntary or based on mutual agreement, while her earnings remain her individual property. From a gender perspective, wives’ participation in supporting the family economy should be accompanied by a proportional redistribution of domestic work and childcare to prevent a double burden. From the perspective of Maqashid al-Shari’ah, such contributions may support the protection of religion, life, intellect, lineage, and property when undertaken lawfully, fairly, and without causing harm. Therefore, financial relations within marriage should be founded on responsibility, reciprocity, consultation, and respect for each spouse’s rights.   Keywords: Wife’s Economic Contribution, Husband’s Responsibility, Maqashid Al-Shari’ah